EFFECT OF LACTOFERRIN ADDITION TO THE SEMEN OF AWASSI RAMS ON SOME PHYSICAL PROPERTIES OF SPERMS - & Houbi, Mahdi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experiment was conducted at the Animal Production Department farm to the College of Agriculture, University of Baghdad, located at Jadreya during the period of 21 September 2015 to 24 February 2016 using Four Awasi rams aged 2-4 years and the average weight was 52 kg. Semen collection from rams was done twice weekly by using the artificial vagina to study the effect of using the lactoferrin protein as a replacement by the antibiotic in the semen for controlling the contamination of bacteria in the semen. Four treated groups were used, the control (normal antibiotic Streptomycin 100 mg\100ml Penicillin 100.000 IU / 100ml) , second ,third and fourth treatment groups was used a lactoferrin  protein with the contamination of 400, 800 and 1200 mg \ L-1 , respectively . All additions of the antibiotic and lactoferrin were done to the semen after dilution. Semen from all rams was pooled and the final volume was divided by four parts to groups .The semen diluent was kept at the refrigerator 5 C for 5 days, and every day the physical characteristic was done which included. The individual motility, dead and abnormal sperm, concentration of sperm, mass activity, integrity of the plasma membrane (HOST %) The results showed that: the individual motility of sperm was significantly increased) for all treated groups on the second, third, fourth and the fifth day of semen preservation. No significant difference  in the percentage of live sperm as a result of adding lactoferrin to the semen. There were no significant increase) in the hyper osmotic sperm test (HOST%) between the control and treatment groups. The abnormality of sperm did not differ between the control and the treated groups.